Improving Understanding of the Definitive Group Needs Plan (RDKK) Through the Role of KKN in Cikole Village, Sumedang - Tati; Wikiari, Vectra Imel; Rodiah, Neng Titin; Alpiani, Neisya Tazkia; Rendy, Asep; Rustandi, Tiffany Asri Hartanti; Karin, Faqihatunnisa Adinda; Firdaus, Mochamad Alif; Rasmana, Idan; Rizki, Friska Putri Indriyani; Sani, Dhiya'an (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This community service aimed to improve farmer group (Gapoktan) understanding of the Definitive Group Needs Plan (RDKK) system in Cikole Village, Sumedang, to address poor distribution of subsidized fertilizers caused by gaps in knowledge and capacity. The goal was to empower Gapoktan so farmers could better access essential agricultural inputs. Method: A qualitative case study with a participatory approach was used, involving field observations, interviews, and a socialization session led by KKN students and the local Agriculture and Food Security Unit. The intervention focused on clarifying Gapoktan’s roles and responsibilities within the RDKK process. Practical Applications: The activity successfully transferred knowledge about the RDKK system, enabling Gapoktan to take direct action in managing their fertilizer needs. Farmer groups shifted from passive recipients to active participants by updating and verifying member data in the e-RDKK system. Conclusion: The KKN program significantly improved Gapoktan’s understanding and sense of responsibility regarding the RDKK, correcting the misconception that registration was solely the task of extension workers. This change supports more accurate, fair, and efficient fertilizer distribution, strengthening local institutional capacity and food security.